Vibration control of a flexible clamped-clamped plate based on an improved FULMS algorithm and laser displacement measurement. (15th June 2016) - Xie, Lingbo; Qiu, Zhi-cheng; Zhang, Xian-min
Abstract: This paper presents a novel active resonant vibration control experiment of a flexible clamped-clamped plate using an improved filtered-U least mean square (FULMS) algorithm and laser displacement measurement. Different from the widely used PZT sensors or acceleration transducers, the vibration of the flexible clamped-clamped plate is measured by a non-contact laser displacement measurement sensor with higher measurement accuracy and without additional load to the plate. The conventional FULMS algorithm often uses fixed step size and needs reference signal related to the external disturbance signal. However, the fixed step size method cannot obtain a fast convergence speed and it will result in a low residual error. Thus, a variable step size method is investigated. In addition, it is difficult to extract reference signal related to the vibration source directly in the practical application. Therefore, it is practically useful that a reference signal is constructed by both the controller parameters and the vibration residual signal. The experimental results demonstrate that the improved FULMS algorithm has better vibration control effect than the proportional derivative (PD) feedback control algorithm and the fixed step-size control algorithm. Highlights: A kind of non-contact vibration measurement for a flexible clamped-clamped plate structure using a laser displacement sensor is proposed. An improved FULMS algorithm is investigated. The advantages of the improved FULMS algorithm are analyzed. It is implemented to suppress the resonant vibration in comparison with other conventional control algorithms. Experimental setup is constructed. Different cases of experiments are carried out to investigate the factors which affect the control performance of the improved FULMS algorithm.